COMPARATIVE STUDY OF PROMOTIONAL MIX AND CONSUMER BUYING BEHAVIOR ON GENDER DIFFERENCES OF SMARTPHONE USERS IN MANADO CITY - Besly, Ryland Valestro (Universitas Sam Ratulangi, 2014)
Communication is the exchange and flow of informations and ideas from one person to another. It is one of the most crucial things in human life. Smartphone is one of the living-proof of the communication development after the invention of mobile phone in early 90’s. The complexity of people’s need particularly in communication is also high. Therefore, smartphone market has been extremely potential with mass of consumers are waiting to be reached by outstanding promotion activities. This study aimed to analyze the difference in consumer behavior on promotional mix based on gender differences of smartphone users in Manado city. The type of this research is comparative study. The target of population was the smartphone users in Manado for the total 100 respondents. Data were collected using questionnaires and analyzed using independent sample t-test. The results from the study show there are no significant differences in consumer behavior on promotional mix based on gender differences of smartphone users in Manado. Thus, author has a few recomendations, namely internet marketing, Coupon/Rebates, Magazine and TV are most effective stimulations and mediums to female consumers buying behavior while newspaper, billboard, poster are most effective way to influenced male consumers buying behavior moreover, smartphone companies can use the data of this research to enhance their promotion channels to specific target market of gender. Smartphone companies for targeting male’s consumer should focus more on informative content. On the other hand, to approach female consumers, the company should focus on emotional content about the product that is being marketed. Keywords: communication, promotional mix, consumer behavior